The fifth discipline : - Senge, Peter M. (Currency Doubleday, 1994)
An MIT Professor's pathbreaking book on building "learning organizations" -- corporations that overcome inherent obstacles to learning and develop dynamic ways to pinpoint the threats that face them and to recognize new opportunities. Not only is the learning organization a new source of competitive advantage, it also offers a marvelously empowering approach to work, one which promises that, as Archimedes put it, "with a lever long enough... single-handed I can move the world."